The new American high school - Sizer, Theodore R. (San Francisco : Jossey-Bass, a Wiley brand, 2013)
"The late Theodore Sizer's vision for a truly democratic public high school systemOur current high schools are ill-designed and inefficient. We have inherited a program of studies that in its overall structure has not changed in over a century. The question is What's next? Theodore Sizer, the founder of The Coalition of Essential Schools, was a passionate advocate for the American school system. In this, his last book, he offers a vision of what a future secondary education might look like. In a book that tells the story of his own odyssey, Sizer gives shape to a much-needed agenda for improving our high schools. Includes a vision for the future of our High Schools from one of America's greatest leaders of educational reform Written by Theodore Sizer founder of The Coalition of Essential Schools and author of landmark book Horace's Compromise This final book from the late Theodore Sizer reveals the man and his vision for our secondary education system"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: High schools -- United States; Education, Secondary -- Aims and objectives -- United States; Educational change -- United States; Electronic books